GRAVITACIONES DE GARCÍA MÁRQUEZ Y SU OBRA ENTRE LOS ESCRITORES DEL CARIBE COLOMBIANO - Castillo Mier, Ariel (Cuadernos de Literatura del Caribe e Hispanoamérica, 2007)
Gabriel García Márquez en los escritores del Caribe colombiano; para ello, inicialmente se retoma la perspectiva que sobre este tema desarrolla el crítico literario Carlos J. María, para luego abordar la obra del premio Nobel de Literatura colombiano, en relación con la de autores como Álvaro Cepeda Samudio, Héctor Rojas Herazo, Germán Vargas Cantillo, Alfonso Fuenmayor, Roberto Burgos Cantor, Germán Espinosa, José Manuel Crespo, Manuel Zapata Olivella, Guillermo Tedio, Eduardo Arango Piñeres, Jaime Manrique Ardila y Ramón Illán Bacca. PALABRAS CLAVES Cultura, influencia, vocación universalista, antiacademicismo, afirmación del ser Caribe. ABSTRACT The goal of this current essay is to analyze the ways in which the influence of Gabriel García Márquez is shown in the writers of the Colombian Caribbean Zone. First, in order to accomplish this, the perspective that on this topic develops the literary critic Carlos J. María is taken into account. Afterwards, the work of the Colombian Nobel Prize of Literature is analyzed in relation with that of authors such as Álvaro Cepeda Samudio, Héctor Rojas Herazo, Germán Vargas Cantillo, Alfonso Fuenmayor, Roberto Burgos Cantor, Germán Espinosa, José Manuel Crespo, Guillermo Tedio, and Jaime Manrique Ardila. KEY WORDS Culture, influence, universalistic vocation, anti-academicism, validation of the Caribbean being.